Developing UAV insurance and risk management strategies - Goldsmith, Grant E. (Kansas State University, 2013)
This presentation from an insurance industry professional covers insuring and managing risk for unmanned air vehicles.
Keywords: Unmanned air vehicles; Insurance; Risk management